Strategi Guru PAK dalam Mengimplementasikan Pembelajaran Berbasis Digital Ditingkat SMP - Yohana Niasty Berutu; Ordekoria Saragih (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study was to determine the strategy of teacher Pak in implementing modern-based learning at the junior high school level. With a qualitative descriptive research method with a literature study approach or library research. Christian Religious Education (PAK) plays a very important role in shaping the character, nature, and behavior of students, and the most important thing is the growth of their faith. Currently, in the twenty-first century, when internet technology is widely used to process information, this has significant consequences for the world of education, with both positive and negative consequences. Digital learning is an effort to improve the quality of learning and not just utilizing digital tools in the classroom. Therefore, digital learning cannot be a trend to use digital tools but a responsibility to improve the quality of learning. By mastering digital competencies and the availability of facilities that support the implementation of digital-based learning, it can be applied maximally and teachers can pour out their creativity to create a new innovation in learning. The limited devices owned by students as a supporter of the learning process are one of the obstacles in implementing technology in the digital transformation era besides signals that we cannot control because not all students are able and come from families with upper economies who at least have android or laptop facilities.